A consistent structure of phytoplankton communities across the warm–cold regions of the water mass on a meridional transect in the East/Japan Sea. (September 2017) - Kwak, Jung Hyun; Han, Eunah; Lee, Sang Heon; Park, Hyun Je; Kim, Kyung-Ryul; Kang, Chang-Keun
Abstract: Three cruises were undertaken along a meridional transect in the East/Japan Sea (EJS) in spring (May 2007), summer (July 2009), and fall (October 2012) to determine the geographic variations in phytoplankton biomass and community composition. This study revealed a gradient of surface temperature and a fluctuation of hydrographic conditions along the transect. Although a subpolar front (SPF) formed between the warm- and cold-water masses (37–40°N), no significant differences in phytoplankton biomass and community composition were detected between the southern and northern parts of the EJS. These results disprove our initial hypothesis that different water masses may contain differently structured phytoplankton communities. In the present study, isothermal layers (≤ 12 °C) fluctuated over a depth of 50 m in both warm- and cold-water masses, depending on the SPF. In contrast, the nitracline (i.e. 2.5 μM nitrate isopleth) depth was recorded within a limited range of 20–40 m in spring, 30–50 m in summer, and 40–60 m in fall. The chlorophyll a concentrations at the subsurface chlorophyll maxima (SCM) were significantly higher in spring and summer (356 ± 233 and 270 ± 182 ng L –1, respectively) than in fall (117 ± 89 ng L –1 ). The relative contributions of individual phytoplankton groups to the depth-integrated chlorophyll a concentration conformed to the composition of the phytoplankton community in the SCM layer, showing a dominance of diatoms (58 ± 19% in spring, 48 ± 11% in summer, and 30 ± 20% in fall). Canonical correspondence analysis revealed that the geographic structures of phytoplankton communities were strongly associated with the vertical structures of water temperature and nutrient concentration in the water column rather than with horizontal gradients of hydrographic conditions. Finally, our findings suggest that water column stability and light–nutrient availability in the euphotic zone play a key role in determining geographical consistency of the biomass and the community structure of phytoplankton in the EJS.